Estudo computacional das interações entre nanopartículas de dióxido de titânio envolvidas no processo de coalescência orientada - Santos, Uallisson Silva (2018)
Experimental and theoretical studies have shown that the aggregation of TiO2 anatase nanoparticles (NPs) occurs with preferential crystallographic orientation by the so-called oriented attachment mechanism (OA). The growth by this process has shown to be important to control the shape of several nanostructured materials, so that one intends to understand the fundamentals of that phenomenon. This way, it has been proposed the construction of realistic models describing the interaction between anatase NPs from a thermodynamic point of view. Five models have been studied, all of them exhibiting a bipyramid truncated morphology with eight (101) facets and two (001) facets, according to Wulff projection. The interactions between the NPs studied have been described by a classical force field comprising Coulomb and Buckingham potentials. Although the size of the models and the numerical efficiency allowed a direct simulation with either Molecular Dynamics or Monte Carlo, preliminary investigations of the potential energy surface revealed multiple minima separated by high barriers of energy, leading to trapped NPs in local minima with a restricted sampling of the available phase space. Thus, an alternative approach has been employed in order to study a thorough and uniform sampling of the space phase, which amounts to the calculation of the partition function of the system. With this procedure it was possible to investigate the profile of energy involved in the process of oriented attachment between the NPs and localize the most and least favorable combinations among their different geometric elements (facets, edges and corners). The obtained results reveal that the combination of two (101) facets represents the most favorable interaction for a dimer of TiO2 anatase NPs. Since experimentally the oriented attachment occurs more commonly on (001) facets than on (101) facets for Wuff-shaped anatase NPs, these results suggest that the NPs are kinetically trapped on local minima separated by high activation energy, since there is a thermodynamic tendency to achieve the global minimum, which corresponds to an interaction between two (101) facets. It has been also observed that border effects due to edges and corners are important for the process of aggregation of nanoparticles, influencing the relative stability of the possible configurations for the system. Furthermore, the process is dominated by interaction energy, since the entropy does not play an important role in the process of coalescence of the studied particles.